# Answer to Question #24245 in Algebra for Mia

Question #24245

What is the solution?

3x - 2y = 6 and 5x + 3y = -9

3x - 2y = 6 and 5x + 3y = -9

Expert's answer

3x - 2y = 6 and 5x + 3y = -9

We can multiply the first equation by 5 and the second by 3. Thus, we obtain

15x-10y=30 and 15x+9y=-27

15x=10y+30 and 15x=-27-9yEquating right parts of equations above we get:

10y+30=-27-9y

19y=-57

Therefore y=-3

As we know 3x-2y=6

3x=2y+6

x=(2y+6)/3=(2*(-3)+6)/3=0

Thus, solution is x=0, y=-3

We can multiply the first equation by 5 and the second by 3. Thus, we obtain

15x-10y=30 and 15x+9y=-27

15x=10y+30 and 15x=-27-9yEquating right parts of equations above we get:

10y+30=-27-9y

19y=-57

Therefore y=-3

As we know 3x-2y=6

3x=2y+6

x=(2y+6)/3=(2*(-3)+6)/3=0

Thus, solution is x=0, y=-3

## Comments

## Leave a comment